Danish: Dronning Marie Thérèse af Frankrig Queen Marie Thérèse of... - Pierre Mignard I (Wikimedia Commons)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Danish: Dronning Marie Thérèse af Frankrig Queen Marie Thérèse of....
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures